Catathrenia (Nocturnal Groaning): A Social Media Survey and State-of-the-Art Review - Alonso, Jose (J Clin Sleep Med, 2017)
STUDY OBJECTIVES: Catathrenia is an underrecognized nocturnal vocalization phenomenon that can be a source of perplexity to patients, bed partners, and medical providers. Catathrenia is distinct from both sleep talking (a parasomnia with loud talking during sleep) and snoring (noise due to vibration of upper airway soft tissues related to variations in airway resistance). The objective of this review is to provide an evidence-based resource to help the practitioner reliably evaluate and manage patients with this condition. METHODS: Data were gathered from: (1) PubMed, Scopus, Web of Science, and Google Scholar; and (2) catathrenia social media groups (Yahoo and Facebook). RESULTS: Data collected were (1) 15 case reports and 17 case series describing 191 patients with catathrenia; (2) questionnaires from 47 catathrenia subjects; (3) 5 audio files. CONCLUSIONS: Catathrenia is a noise produced during sleep (distinct from snoring) with identifiable harmonics, a computable main frequency, and high-decibel intensity that involves active adduction and vibration of the vocal cords during expiration. The quality of groaning in catathrenia is monotone, and often presents with a morose or sexual connotation, causing a significant social problem for patients. Although there is no association with risk of physical harm, catathrenia does present a significant disturbance to the bed partner and has been associated with subjective impairments to sleep quality, including unrefreshing sleep and fatigue. Polysomnography can be useful if performed properly to confirm the diagnosis and to evaluate for comorbid sleep disturbances, such as obstructive sleep apnea or parasomnia. Directions for further research could involve consideration of deep breathing exercises, yoga, meditation, or myofunctional therapy to help abate symptoms. CITATION: Alonso J, Camacho M, Chhetri DK, Guilleminault C, Zaghi S. Catathrenia (nocturnal groaning): a social media survey and state-of-the-art review. J Clin Sleep Med. 2017;13(4):613–622.